2011
DOI: 10.1111/j.1757-5672.2011.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Severity of Atherosclerosis and Lower Urinary Tract Function in Male Patients with Lower Urinary Tract Symptoms

Abstract: Development of atherosclerosis impairs both voiding and storage function independently of age, suggesting atherosclerosis leads to lower urinary dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 28 publications
0
34
0
1
Order By: Relevance
“…A study with Japanese patients showed similar findings in that the maximum flow rate in men with atherosclerosis assessed by ultrasound examination of the carotid artery was significantly lower than that in the men without it (13.4 ± 5.5 mL/s vs. 16.7 ± 7.7 mL/s). This Japanese study also showed the daytime frequency of urination to be significantly higher in the men with atherosclerosis than in those without it (7.13 ± 3.02 times vs. 8.75 ± 2.50 times), although nocturia was not evaluated 26 . These findings indicate that atherosclerotic disease may play a significant role in the impairments of both voiding and storage function in male patients.…”
Section: Discussionmentioning
confidence: 76%
“…A study with Japanese patients showed similar findings in that the maximum flow rate in men with atherosclerosis assessed by ultrasound examination of the carotid artery was significantly lower than that in the men without it (13.4 ± 5.5 mL/s vs. 16.7 ± 7.7 mL/s). This Japanese study also showed the daytime frequency of urination to be significantly higher in the men with atherosclerosis than in those without it (7.13 ± 3.02 times vs. 8.75 ± 2.50 times), although nocturia was not evaluated 26 . These findings indicate that atherosclerotic disease may play a significant role in the impairments of both voiding and storage function in male patients.…”
Section: Discussionmentioning
confidence: 76%
“…Basic research evidence of detrusor overactivity and voiding dysfunction in bladder ischemia has been supported by clinical observations of a close relationship between human lower urinary tract ischemia and LUTS 1219. In clinical studies, lower urinary tract blood flow has been measured and bladder ischemia documented in elderly patients with LUTS 1219.…”
Section: Discussionmentioning
confidence: 93%
“…In clinical studies, lower urinary tract blood flow has been measured and bladder ischemia documented in elderly patients with LUTS 1219. Decreased bladder blood flow significantly correlated with LUTS in both men and women 1217.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have investigated the association between LUTS and vascular risk factors for atherosclerosis such as hypertension, hyperlipidemia, diabetes mellitus and nicotine use 100, 101 , and Ponholzer et al (2006) suggested the potential role of atherosclerosis in the development of LUTS in both sexes 100 . Takahashi et al (2012) also indicated the association between severity of atherosclerosis and male LUTS 102 . Pinggera et al (2006), using transrectal color Doppler ultrasonography, showed that elderly patients with LUTS had a significant decrease in bladder blood flow compared with asymptomatic young individuals 103 .…”
Section: Risk Factorsmentioning
confidence: 98%